Input Use under Crop Insurance: The Role of Actual Production History. (26th June 2018) - Mieno, Taro; Walters, Cory G.; Fulginiti, Lilyan E.
Abstract: The impact of crop insurance on changes in input use has attracted much attention by economists. While there are a number of studies on this topic, they frame moral hazard in inputs use in a static model. However, when agricultural producers are forward‐looking, they would make input allocation decisions realizing that their decisions would affect their future actual production history. This, in turn, affects the probability and size of future indemnity payments. Thus, moral hazard should be framed in a dynamic input use decision model. We first show theoretically that under certain feasible conditions, a static analysis always results in lower optimal input use when compared to a dynamic one with endogenous actual production history. This is because static models fail to recognize the role of actual production history. We then run numerical simulations using nitrogen application rates as a case study. We find that static models indicate significant reduction in nitrogen use compared to the no‐insurance scenario, whereas the dynamic models with a role for actual production history indicate almost no reduction in applied nitrogen. The dynamic analysis not only suggests a near absence of moral hazard, but, for low coverage rates, it results in an optimal nitrogen rate higher than that under the no‐insurance scenario. These findings illustrate the importance of recognizing the role of actual production history in mitigating moral hazard possibilities in crop insurance and the dynamic nature of moral hazard in crop insurance.